The Goshree Road Link, Kochi, India: A Design Approach towards Creating a Legible Streetscape - Arun George; Amita Sinha ; Varkki George Pallathucheril (Journal of Urban Design, Vol. 10. No. 2, 275-288, June 2005, 2005)
Kochi, the commercial capital of Kerala, is one of the busiest seaports in India, and is believed to be one of the fastest growing regions in the country. To connect the islands-Bolghatty and Vallarpodam-and Vypeen peninsula in the backwaters to mainland Kochi, a road link is proposed. Since the road will weave through diverse landscapes-urban, suburban, rural and waterfront-the challenge lies in designing such that it blends with the surrounding landscape, accommodates existing patterns of behaviour and inhibits dangerous encounters between people, animals and vehicles, common in Indian streets. Monumental streets stretching between visually prominent foci of power-historic and modern-in temple cities, Shahjahanabad and boulevards of New Delhi and Chandigarh, form precedents for environmental legibility and a vivid sense of place. The tensions between the public and the private realm and between high speed and slow moving traffic can be resolved in a multiway boulevard.